2013
DOI: 10.1016/j.worlddev.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The Resource Curse and its Potential Reversal

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(92 citation statements)
references
References 52 publications
5
82
0
5
Order By: Relevance
“…16 We have also administered two surveys to all individuals in the experiment. 17 The first survey was collected either one or three months after individuals were subjected to randomization, and is mainly focused at capturing differences in working methods, but also collects information on short run employment outcomes. 18 The second survey was administered three months after the longest potential treatment at a private placement agency; which means nine (six) months after randomization for immigrants and disabled (adolescents).…”
Section: 2mentioning
confidence: 99%
“…16 We have also administered two surveys to all individuals in the experiment. 17 The first survey was collected either one or three months after individuals were subjected to randomization, and is mainly focused at capturing differences in working methods, but also collects information on short run employment outcomes. 18 The second survey was administered three months after the longest potential treatment at a private placement agency; which means nine (six) months after randomization for immigrants and disabled (adolescents).…”
Section: 2mentioning
confidence: 99%
“…Several studies found the resource curse to disappear under strong institutions (Mehlum et al, 2006a;Apergis and Payne 2014;Bhattacharyya and Collier 2014;Sarmidi et al, 2014) and concluded that abundance may even foster economic growth. (Szalai, 2011;Boschini et al, 2013) Hence, political economy models are plausible candidates to resolve the monotony problem. See Section 4 for further discussion.…”
Section: Evolution Of the Literaturementioning
confidence: 99%
“…For instance, several papers suggest that the negative relationship between natural resource intensity and economic growth can be reversed if institutional quality is high enough (Boschini et al, 2013). Lederman and Maloney (2002) also argue that the negative correlation between natural resources and economic growth might be contingent on the choice of natural resources indicators and also due to international heterogeneity in the effects of natural resources on economic growth.…”
Section: The Determinants Of Economic Growth In Coastal Countries Witmentioning
confidence: 99%
“…For instance, several papers suggest that the negative relationship between natural resource dependence and economic growth can be reversed if institutional quality is high enough (Boschini et al, 2013). Natural resourcedependent countries constitute both growth losers and growth winners, and some authors argue that the main difference between the success cases and the cases of failure would lie in the quality of institutions and in the political economy (Melhum et al, 2006 andTorvik, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation